Surface Sites Distribution on Chlorogenic Acid Imprinted Polymers Based on Langmuir-Freundlich Isotherm Model by Frontal Liquid Chromatography Technique - Tang, Siping; Li, Hui; Xu, Zhifeng; Lu, Cuimei (Asian Journal of Chemistry, 2015)
Surface sites distribution on chlorogenic acid (CGA) imprinted polymers (MIPs) was investigated under various temperature and mobile phase composition based on the best fitting parameters of Langmuir-Freundlich (LF) model to adsorption isotherms obtained by frontal chromatography technique. Curves of sites number towards sites energy distribution under different conditions were plotted by using the best Langmuir-Freundlich fitting values and total sites number, affinity constant and heterogeneity index for this MIPs. Results indicated that for various compounds, the most suitable sites occupied were of difference in sites energy distribution and total sites number and its energy distribution varied. For the template, total sites number on the MIPs decreased when measurement was performed at higher temperature or/and using higher concentration of acetic acid in mobile phase. Additionally, structure character of analytes like molecular size, shape, functional group type and number and mass transfer dynamic were shown to influence the binding capability of compounds on imprint sites.